CNC LATHE PROGRAMMING: DESIGN AND DEVELOPMENT OF PROGRAM CODE FOR SIMULATING LINEAR INTERPOLATION MOTION (Balkan Journal of Applied Mathematics and Informatics, 2025)
This paper builds upon the foundational work of simulating linear interpolation motion in CNC turning by advancing into the realm of CNC lathe programming. It focuses on the design and development of program code specifically tailored for simulating linear interpolation motion. By integrating G-code programming techniques with advanced simulation tools, this study provides a robust framework for visualising and analysing the precise motion paths in CNC lathe operations. The results contribute to improved accuracy and efficiency in CNC machining processes, offering valuable insights for both academic research and practical applications in the field of CNC programming.
Keywords: Material removal, Metal cutting, Turning, G-codes, Program blocks